Need assessment in practice: Methods, experiences and trends - Horst Geschka; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 1999)
The intensive concern with customer needs and problems is one of the key contributors to the success of innovation management. During the seventies, numerous procedures were developed, in theory as well as in practice. These procedures entered literature as so called need-assessment approaches (see e.g. Holt, Geschka, Peterlongo 1984). However, the application of these procedures to different industrial sectors and types of firms as well as the benefit achieved for innovation in practice, remained unexplored to a great extent till the nineties, except for a few documented experiences and case studies (see e. g. Herstatt 1998). Geschka and Herstatt carried out the first empirical study in Switzerland in 1990/91. This study was confined to the Swiss mechanical industry and the results were published in Die Unternehmung 3/91 (Geschka, Herstatt 1991). An identical survey was repeated in 1998 within the scope of a research project together with the Institute of International Innovation Management of the University of Bern. The scope was extended to the chemical industry and the electrical industry. Some results from the first study were confirmed. Nevertheless, differences were noticed as well, especially with regard to the use of several methods to record innova-tion needs, it was also found that different industries have different preferences with respect to methods due to specifics of the branch. In this paper, we describe the results of the current study, go into the differences between both studies, and discuss these and the possible ration-als in the interviewed companies.
urn:nbn:de:gbv:830-opus-1649
Keywords: 650; innovation management; need-assessment